2016
DOI: 10.1177/1932296816633720
|View full text |Cite
|
Sign up to set email alerts
|

Event and Cost Offsets of Switching 20% of the Type 1 Diabetes Population in Germany From Multiple Daily Injections to Continuous Subcutaneous Insulin Infusion

Abstract: Background: Most patients with type 1 diabetes (T1D) administer insulin by multiple daily injections (MDI). However, continuous subcutaneous insulin infusion (CSII) therapy has been shown to improve glycemic control compared with MDI. Objective: The objective was to determine the key medical event and cost offsets generated over a 4-year period by introducing CSII to T1D patients who have inadequately controlled glucose metabolism on MDI in Germany. Methods: A decision-analytic budget impact model, simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…5 At first, when CSII was marketed, it was expected to be proposed only to patients with type 1 diabetes mellitus; however, in the latest years, the use of CSII is spreading also among type 2 diabetic patients, due to the good results reported in an analysis from the OpT2mise randomized trial. 6 Furthermore, Zollner et al 7 showed that the use of CSII resulted in fewer severe hypoglycaemic events requiring hospitalization and complication-borne diabetic events compared with multiple daily injection (MDI). The incurred CSII implementation costs are hence offset to a substantial degree by cost savings in complication treatment.…”
Section: Introductionmentioning
confidence: 99%
“…5 At first, when CSII was marketed, it was expected to be proposed only to patients with type 1 diabetes mellitus; however, in the latest years, the use of CSII is spreading also among type 2 diabetic patients, due to the good results reported in an analysis from the OpT2mise randomized trial. 6 Furthermore, Zollner et al 7 showed that the use of CSII resulted in fewer severe hypoglycaemic events requiring hospitalization and complication-borne diabetic events compared with multiple daily injection (MDI). The incurred CSII implementation costs are hence offset to a substantial degree by cost savings in complication treatment.…”
Section: Introductionmentioning
confidence: 99%